In or Out of Equilibrium? How Microbial Activity Controls the Oxygen Isotopic Composition of Phosphate in Forest Organic Horizons With Low and High Phosphorus Availability - Pistocchi, Chiara; Mészáros, Éva; Frossard, Emmanuel; Bünemann, E. K.; Tamburini, Federica (Frontiers in Environmental Science, 2020)
While there are estimates of the abiotic processes contribution to soil phosphorus (P) availability, less is known about the contribution of biological processes. Two main enzymatic processes involved in soil P cycling are known to alter the oxygen isotopic composition of phosphate (δ18O-P), each in a different way, through the cleavage of the P–O bond: the intracellular P turnover and the organic P hydrolysis. The former induces isotopic equilibration between phosphate and water and is considered the major process affecting soil available P via microbial P release. The latter induces depleted δ18O-P in the phosphate released from the mineralization of organic P. We studied P dynamics in organic horizons of two contrasting soils (low- and high-P availability) from temperate beech forests. We labelled the soil with 18O-enriched water and followed changes in the δ18O-P of different soil P pools in the presence or absence of added leaf litter during three months of incubation. δ18O-P values of almost all P pools progressively increased indicating oxygen incorporation from the enriched soil water into phosphate via the above-mentioned enzymatic processes. δ18O-P of available P increased more in the P-rich soil than in the P-poor soil and approached the isotopic equilibrium between phosphate and water, revealing the impact of microbial P release into the available P. However, in the P-poor soil, the available P brought the signature induced by phosphatase enzymes, indicating that it was mostly originated from the hydrolysis of organic P. Therefore, a below-equilibrium signature can be still an indicator of control of microbial P on the available P via Po hydrolysis reactions. Finally, two independent isotopic approaches with 33P and δ18O-P provided very similar estimates of P exchanged between the available P and other inorganic soil pools. This suggests that δ18O-P can be successfully used to trace P fluxes, provided that the underlying processes do not break the P – O bonds of the phosphate molecule.